Matrikkelitaiteilijaksi valikoituminen : Suomen Kuvaamataiteilijat -hakuteoksen (1943) kriteerit - Jämsänen, Auli (2006)
This thesis examines how the students of the Drawing School of the Finnish Art Society were selected for the Biographical Encyclopedia of Filmish Artists published by the Artists' Association of Finland in 1943. Thus it focuses on the artistic practises in Finland between 1902 and 1943, and on the practices of selecting the artists for the Encyclopedia. For this study, the students were selected from the rush years of 1902-1904, when altogether 117 students (56 females/61 males) were enrolled for a probationary period at the Drawing School. Thirty-one of them are included in "Suomen Kuvaamataiteilijat" (Finnish Artists Encyclopedia) published in 1943. As the first Biographical Encyclopedia of Artists in Finland, this book has been a cornerstone of later encyclopedias and a criterion of who is and who is not a "professional" artist. The object of this thesis is to investigate what criteria excluded artists from the Encyclopedia. The main material of the thesis comes from the Archives of the Artists' Association of Finland. Documents of art schools, newspaper articles and letters are also used as sources. The professional self-image of the students was also revealed in other documents, such as telephone directories or even church registers. 11,e sociological theory of Pierre Bourdieu is used as the analytical framework. Howard S. Becker's and Robert A. Stebbings's definitions are used to analyse artists and amateurs. The early stages of the Encyclopedia reveal the struggles taking place in the Finnish art field in the 1930s. Through the Fim1ish Artists Encyclopedia, the Artists' Association of Finland took over the monopoly of producing artists on the battleground of art. The intention of the Artists' Association of Finland was to distinct the "true artists" from the artists of "doubtful" reputation. The reputation as an artist was not based on the artists' works but on where his/her works was distributed. The first criterion was being shown three times in the juried exhibitions organised by the Artists' Association of Finland or the Finnish Art Society. The artists who distributed their works themselves in provinces and organised private exhibitions, and artists who were blamed to be copiers and mass-producers were excluded. Also artists with no public burden of bad reputation were excluded, and some even at random.